Extracellular HMGB1 Impairs Macrophage-Mediated Efferocytosis by Suppressing the Rab43-Controlled Cell Surface Transport of CD91 - Wang, Yao; Zhang, Wen; Xu, Yu; Wu, Di; Gao, Zhan; Zhou, Jianchun; Qian, Hang; He, Binfeng; Wang, Guansong (Frontiers in Immunology, 2022)
High mobility group box-1 protein (HMGB1) has been considered as a phagocyte suppressant for suppressing the clearance of apoptotic cells by macrophage, delaying inflammation resolution in the lungs and aggravating the progress of ALI/ARDS. However, the precise mechanism is still unknown. Here, we found that HMGB1 impaired phagocytosis apoptotic cells (ACs) by BMDMs and suppressed Rab43 level which was a member of Rab family. Rab43 deficiency also impaired phagocytosis apoptotic thymocytes (ATs) by BMDMs. Further study revealed that CD91, phagocytic recognition receptor, could not be transported to cell surface from cytoplasm in HMGB1 treated- or Rab43 deficiency BMDMs. Rab43 interacted directly with CD91, and mediated CD91 intercellular trafficking. Furthermore, Rab43 deficiency delayed inflammation resolution and worsened lung tissue damage in ALI mice model. Together, our results provide evidence that HMGB1 impaired macrophage phagocytosis and delayed inflammation resolution through suppressing Rab43 mediated anterograde transport of CD91, suggesting that restoration of Rab43 levels is a promising strategy for attenuate acute lung injury.